Numerical and experimental wind tunnel analysis of aerodynamic effects on a semi-submersible floating wind turbine response - Fontanella A.; Bayati I.; Taruffi F.; Facchinetti A.; Belloli M. (Volume 10: Ocean Renewable Energy, 2019)
This paper presents the main results of an experimental campaign about the DeepCwind semi-submersible floating offshore wind turbine (FOWT), that was carried out at Politecnico di Milano wind tunnel, adopting a hybrid hardware-in-the-loop (HIL) testing technique. Differently from previous works by the authors, this further analysis herein reported, is specifically focused on evaluating the effects of aerodynamic loads on the FOWT platform motions. In order to reproduce the FOWT response to combined wind and waves in a wind tunnel, exploiting the high-quality flow, a HIL system was used. The aerodynamic and rotor loads were reproduced by means of a wind turbine scale model operating inside the wind tunnel and were combined with numerically generated wave loads for real-time integration of the FOWT rigid-body motion equations. The resulting platform motions were imposed to the wind turbine scale model by a hydraulic actuation system. A series of HIL tests was performed to assess the rotor loads effect on the FOWT response. Free-decay tests in still water under laminar un-sheared wind were carried out to evaluate how the aerodynamic forcefield modifies the platform modes frequency and damping. Irregular wave tests for different steady winds were performed to investigate the dependency of platform motion from the wind turbine operating conditions. A FAST v8 model of the studied floating system was developed to support the analysis and numerical simulations were performed to reproduce environmental conditions equivalent to those of the experimental tests. The FAST model prediction capability is discussed against HIL wind tunnel tests results.